Sensitivity of Pseudomonas aeroginosa Isolated from patients with different clinical state to Antibiotics and determination of some virulance factors in vitro - Waad M. Raoof; A.L. Shameran M. Tawfiq (Tikrit Journal of Pure Science, 2023)
Present study was conducted on 65 isolates belonging to the bacteria P.aeruginosa which included 30 isolates by (46%) of burns, 20 (30%) isolated from urinary tract infections15 (23%) of middle ear infections , tested the sensitivity of the isolates towards (19) antibiotic belonging to (6) groups for different isolates showed a clear divergence in different proportions and in their resistance to antibiotics. It showed antibiotics (Cfepime, Ceftazidim, Imepenime, Amikacin, Tobramicin, Ciprofloxacin, Ofloxacin, Norfloxacin) the most efficient antibiotics used, either antibiotics (Gentamicin ,Streptomycin, Cefixim Augmentin, Cefotaxim, Tobramicin) was medium efficiency either (Cefotetan, Carbencilin, ceftriaxone, Azatrionam, Naldixic acid Piprasilin) was the lowest influential . expressed, 100% of all isolates have ability to produce the enzyme Coagulase and (92.30 %) for each of the enzyme (Licithenase, Haemolycin and Protease), while showed (84.61 %) of the isolates were positive for the examination of enzyme β-lactamase.